2016
DOI: 10.1007/s10096-016-2590-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative hospital-based observational study of mono- and co-infections of malaria, dengue virus and scrub typhus causing acute undifferentiated fever

Abstract: Positive serology for dengue and/or scrub typhus infection with/without positive malarial smear (designated as mixed or co-infection) is being increasingly observed during epidemics of acute undifferentiated febrile illnesses (AUFIs). We planned to study the clinical and biochemical spectrum of co-infections with Plasmodium sp., dengue virus and scrub typhus and compare these with mono-infection by the same organisms. During the period from December 2012 to December 2013, all cases presenting with AUFIs to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 20 publications
5
50
0
Order By: Relevance
“… 13 In our study patients with co-infection had hypoalbuminemia, but none of them fulfilled the criteria for severe scrub typhus. Similar to findings of the present study, elevated transaminases (AST > ALT), bilirubin and alkaline phosphatase were also noted in the study by Ahmed et al and a case of dengue – scrub co-infection reported by Iqbal et al 4 , 5 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 13 In our study patients with co-infection had hypoalbuminemia, but none of them fulfilled the criteria for severe scrub typhus. Similar to findings of the present study, elevated transaminases (AST > ALT), bilirubin and alkaline phosphatase were also noted in the study by Ahmed et al and a case of dengue – scrub co-infection reported by Iqbal et al 4 , 5 …”
Section: Discussionsupporting
confidence: 92%
“…Duration of fever, mean age of presentation and male to female ratio in our study were similar to the study by Ahmed et al 4 Abdominal pain was a common clinical manifestation in the above study, whereas headache was the common clinical feature apart from fever in our study. Patients with co-infection had symptoms indistinguishable from isolated dengue fever.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Malaria, dengue, and chikungunya are the most common coinfections reported from India [17]. Scrub typhus, malaria, dengue fever, and leptospirosis coinfections have been reported from Himachal Pradesh, Uttarakhand, central India, Puducherry, and also from other parts of India [2,[18][19][20][21][22]. The prevalence of coinfections among patients with AUF was 1.39% in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Little is known about the clinical significance of coinfections as compared to monoinfections. Conflicting reports about the severity of illness have been observed in different studies [18,25,26]. We could not draw any conclusion on the clinical significance of concurrent coinfections in our study, as monoinfections were not studied as controls.…”
Section: Discussionmentioning
confidence: 68%